Reasons to choose Computing in Brazil: an Intersectional Study across Areas of Interest - Carvalho, Pâmela; Moro, Mirella M. (Anais do Women in Information Technology (WIT); 2026: Anais do XX Women in Information Technology, 2026)
This study examines how multiple factors influence the choice of specific Computing subfields through a questionnaire-based survey. Our analysis follows a three-step approach: gender-based response distribution; intersectional analysis by age, race, and region; and comparative professional profiling. By identifying the factors that attract or discourage women, this work provides insights to inform recruitment and retention strategies.